Perancangan Interior Sekolah Bola Basket Archo di Surabaya - Adi Santosa, Denny Yuwono Chandra (Intra, 2014)
Surabaya, who received the title as a warehouse in East Java and National athlete, became one barometer sport in Indonesia, one of the sport of basketball. Archo basketball school located in Surabaya, is one tool that can accommodate people of Surabaya in coaching basketball athletes from an early age until later able to become national athletes who excel and be the name of Indonesia in the international basketball world. But unfortunately this is not a basketball school has adequate facilities for teaching and learning activities. Where during this school basketball ARCHO still renting the field to make learning and teaching activities and at the rental places still do not have the facilities - facilities that support for teaching and learning. Therefore, designing a building that has a wide range of facilities that can support teaching and learning in the school basketball is very important because this is not a basketball school has its own building designers use the design architect of the building plans.